Canal-centring ability of three rotary file systems in simulated curved canals: A comparative study - Khalilak Zohreh; Alavi Kaveh; Akhlaghi Nahid; Mehrvarzfar Payman; Dadresanfar Bahareh (Wolters Kluwer Medknow Publications, 2009)
Objective: To compare the canal-centring ability of M two , ProFile and RaCe rotary files, in simulated curved canals. Materials and Methods: About 30 simulated canals were prepared by M two , ProFile and RaCe rotary files. Pre and post-operative pictures were super-imposed and transportations recorded. Measurements were carried out at five different points: Canal orifice (O); half-way to the orifice in the straight section (HO); the beginning of the curve (BC); the apex of the curve (AC); the end point (EP). Intra- and inter-group comparisons were carried out by Wilcoxon`s signed ranks test and Kruskal-Wallis test respectively, using SPSS 14.0 software. Results: ProFile did not change canal centricity in any point. RaCe kept centricity at HO, BC, AC and EP. M two changed canal centricity in points BC, AC and EP. M two group kept the centricity significantly less than the other two groups at BC (P = 0.004), AC (P = 0.015) and EP (P = 0.01). There was no significant difference between these three rotary files at HO. However, the difference between RaCe, M two and ProFile was significant at O (P = 0.015). Conclusion: ProFile and RaCe rotary files remained better centred than M two rotary files